Site visit to VIVA City Mall Kuching - Jiin Yih, Yeo; Abdul Rahman, Siti Hamidah (UiTM Sarawak, 2016)
On 7th September 201 5, Madam Siti Hamidah led a team of 48 students taking the course of Construction Building III to the Viva City Mall, Kuching. The main objective of the site visit was to expose students to the concept of Industrial Building System (IBS) and its application in the construction industry. IBS is a construction process that utilizes techniques, products, components, or building systems which involve mainly the prefabricated components and onsite installation.